1994
DOI: 10.1007/bf01416093
|View full text |Cite
|
Sign up to set email alerts
|

Desorption and plant-availability of phosphate sorbed by some important minerals

Abstract: Experiments were conducted to study the desorption characteristics and plant-availability of phosphate sorbed by some important variable-charge minerals including kaolinite, goethite and amorphous A1 oxide. Phosphate desorption from the complexes of goethite-P, kaolinite-P and A1 oxide-P by equilibration with 0.02 M KC1, resin or some commonly used chemical extractants was slow compared to desorption from a permanent-charge mineral (montmorillonite). However, rice plants were not observed under P deficiency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
4
21
0
4
Order By: Relevance
“…Therefore, increasing K d is interpreted as increasing the rate of change in P desorption at a particular solution P concentration, as was observed for all levels of P loading when soil pH was raised to 7.1. Similar results can be found among the limited P desorption studies previously reported (He et al, 1994;De Smet et al, 1998).…”
Section: Soil Ph Effect On P Desorptionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, increasing K d is interpreted as increasing the rate of change in P desorption at a particular solution P concentration, as was observed for all levels of P loading when soil pH was raised to 7.1. Similar results can be found among the limited P desorption studies previously reported (He et al, 1994;De Smet et al, 1998).…”
Section: Soil Ph Effect On P Desorptionsupporting
confidence: 91%
“…Increased pH levels to 6.0 and 7.1 caused the release of an additional 0.2 to 1.0 and 0.7 to 2.7 kg ha -1 of sorbed P into soil solution for prompt plant uptake. These results are consistent with the findings of He et al (1994). He and associates determined P desorption from a variety of minerals and ranked the minerals according to their desorption capacity: goethite < kaolinite < amorphous Al oxide < montmorillonite.…”
Section: Soil Ph Effect On P Desorptionsupporting
confidence: 89%
“…Because of strong adsorption and occlusion of phosphate by Fe and Al oxides, the utilization efficiency of applied and indigenous soil P to crops is very low (<5-15%) (Lin, 1995). Phosphorus deficiency is one of the critical soil constraints to crop production in the red soil regions (He et al, 1990(He et al, , 1994(He et al, , 1996. Development of adequate chemical and biochemical index of P availability is critical for enhancing crop production on the red soils.…”
Section: Introductionmentioning
confidence: 98%
“…Anion exchange materials have been used to investigate the desorption kinetics of P (Raven and Hossner, 1994), measure P mineralization (Parfitt et al, 1994), and measure total resindesorbable P by sequential extraction (He et al, 1994). However, P desorption isotherms using AEMs have seldom been developed.…”
Section: Introductionmentioning
confidence: 99%